2021
DOI: 10.1007/s40744-021-00332-w
|View full text |Cite
|
Sign up to set email alerts
|

Baricitinib and the Risk of Incident Interstitial Lung Disease: A Descriptive Clinical Case Report from Clinical Trials

Abstract: Objectives: Interstitial lung disease (ILD) occurs in up to 30% of patients with rheumatoid arthritis (RA), resulting in increased morbidity and death in the absence of proven therapies. The aim of this study is to estimate the number of incident ILD cases reported through development studies with baricitinib in patients with RA. Methods: Estimates were based on 3770 patients with RA from eight randomized clinical trials (four phase 3, three phase 2, one phase 1b) and one long-term extension study on baricitin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 22 publications
0
4
0
1
Order By: Relevance
“… 45 Furthermore, baricitinib treatment for RA patients is associated with a low risk of developing noninfectious ILD, similar to what has been observed with other jak inhibitors. 46 It is anticipated that JAK inhibitors can boost hope for RA‐ILD patients as more research into them is conducted.…”
Section: Discussionmentioning
confidence: 99%
“… 45 Furthermore, baricitinib treatment for RA patients is associated with a low risk of developing noninfectious ILD, similar to what has been observed with other jak inhibitors. 46 It is anticipated that JAK inhibitors can boost hope for RA‐ILD patients as more research into them is conducted.…”
Section: Discussionmentioning
confidence: 99%
“…Baricitinib is a JAK1/JAK2 inhibitor suggested as a treatment for patients with RA-ILD who do not respond to the initial treatment with MTX [ 120 ]. An analysis of 3770 patients with RA from eight randomized clinical trials and one long-term extension study on baricitinib showed promising effects in lowering the risk of ILD development [ 121 ]. When 11 patients with RA and 4 patients with RA-ILD were treated with baricitinib for 6 months, a considerable decrease in inflammation was observed in patients with RA-ILD via a reduction in KL-6, which is a biomarker of RA-ILD.…”
Section: Targeted Synthetic Dmards (Jak Inhibitors)mentioning
confidence: 99%
“…In a descriptive, multicentric, retrospective cohort study that included data pooled from eight randomized trials, with 3770 RA patients treated with baricitinib, with 12,358 patient-years of exposure, Salvarani et al identified 21 ILD cases with an exposure-adjusted incidence rate (EAIR) of 0.17 per 100 patient-years of exposure (PYE), proving a low risk of developing ILD during treatment [ 65 ].…”
Section: Targeted-synthetic Dmards/janus Kinase Inhibitorsmentioning
confidence: 99%